Some structural characteristics of pre-monsoon depression in the Bay of Bengal - BHOWMIK , S. K. ROY; MISHRA, P. K. (MAUSAM, 1999)
During the period 6 to 16 May. 1995. three deep depressions formed one after another over west Bay of Bengal and moved from south to north. In this paper, structural characteristics of these systems are investigated from the distribution of thermal and thermodynamical field observed around the depression center utilising daily Rs/Rw and other available coastal observations during the period, Major findings of the study are: (i) The depressions have low level cold core and middle and upper tropospheric warm core. (ii) Thermal and moisture fields tilt north ward with height but vertical tilt of contour height is .not uniform at all levels, (iii) During intensification of the system significant increase in temperature and moisutre occurs above 700 hPa and significant fall of contour height occurs below 300 hPa.